Dissection of Synechococcus rubisco large subunit sections involved in holoenzyme formation in Escherichia coli by combinatorial section swapping and sequence analyses - Yeap, Yee Hung; Koay, Teng Wei; Wong, Hann Ling; Lim, Boon Hoe (Penerbit Universiti Kebangsaan Malaysia, 2018)
Engineering the CO2-fixing enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) to improve photosynthesis has long been sought. Rubisco large subunits (RbcL) are highly-conserved but because of certain undefined sequence differences, plant Rubisco research cannot fully utilise the robust heterologous Escherichia coli expression system and its GroEL folding machinery. Previously, a series of chimeric cyanobacteria Synechococcus elongatus Rubisco, incorporated with sequences from the green alga Chlamydomonas reinhardtii, were expressed in E. coli; differences in RbcL sections essential for holoenzyme formation were pinpointed. In this study, the remaining sections, presumably not crucial for holoenzyme formation and also the small subunit (RbcS), are substituted to further ascertain the possible destabilising effects of multiple section mutations. To that end, combinations of Synechococcus RbcL Sections 1 (residues 1-47), 2 (residues 48-97), 5 (residues 198-247) and 10 (residues 448-472), and RbcS, were swapped with collinear Chlamydomonas sections and expressed in E. coli. Interestingly, only the chimera with Sections 1 and 2 together produces holoenzyme and an interaction network of complementing amino acid changes is delineated by crystal structure analysis. Furthermore, sequence-based analysis also highlighted possible GroEL binding site differences between the two RbcLs.